Professional Governance in a Time of Crisis. (April 2022) - Porter-O'Grady, Tim; Pappas, Sharon
Abstract : The global COVID-19 health crisis has significantly altered the structures and processes of healthcare in innumerable unanticipated ways. No profession has been more impacted or challenged than nursing. In many settings, nursing professional governance has been abandoned or neglected. The impact of this trend is outlined in this article. The authors suggest to nurse leaders that nursing professional governance can be an invaluable mechanism for nursing engagement in the midst of managing a crisis.